2014
DOI: 10.1021/ac500163f
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube-Loaded Nafion Film Electrochemical Sensor for Metal Ions: Europium

Abstract: A Nafion film loaded with novel catalyst-free multiwalled carbon nanotubes (MWCNTs) was used to modify a glassy carbon (GC) electrode to detect trace concentrations of metal ions, with europium ion (Eu(3+)) as a model. The interaction between the sidewalls of MWCNTs and the hydrophobic backbone of Nafion allows the MWCNTs to be dispersed in Nafion, which was then coated as a thin film on the GC electrode surface. The electrochemical response to Eu(3+) was found to be ∼10 times improved by MWCNT concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 34 publications
1
42
1
Order By: Relevance
“…The cathodic (E pc ) and anodic peak (E pa ) potentials were observed at 598 mV and 768 mV, respectively. Wang et al [41] reported on the carbonnanotube loaded Nafion film for the detection of europium where the redox peak potentials were recorded as 600 and 800 mV respectively and this report is in lines to our present work. The separation of the peak potential (E pc − E pa ) is found to be 0.170 V and this confirms the fast electron transfer kinetics.…”
Section: Confirmation Of the Presence Of Europium Ionsupporting
confidence: 92%
See 1 more Smart Citation
“…The cathodic (E pc ) and anodic peak (E pa ) potentials were observed at 598 mV and 768 mV, respectively. Wang et al [41] reported on the carbonnanotube loaded Nafion film for the detection of europium where the redox peak potentials were recorded as 600 and 800 mV respectively and this report is in lines to our present work. The separation of the peak potential (E pc − E pa ) is found to be 0.170 V and this confirms the fast electron transfer kinetics.…”
Section: Confirmation Of the Presence Of Europium Ionsupporting
confidence: 92%
“…At lower pH conditions, the coexisting cations, such as H + will compete with the ion-exchange sites of Nafion with Eu 3+ . At the higher level, the excess OH − ions will cause the hydrolysis of Eu 3+ [41,42]. In order to evaluate this situation in our present work, various pH values of 0.1 M acetate buffers were examined and the results showed a similar value of peak current over the range of pH 3.5-4.5.…”
Section: Confirmation Of the Presence Of Europium Ionmentioning
confidence: 86%
“…An ideal example is europium (Eu), which has numerous applications due to its electronic and optical properties [1]. Many current methods for detection of Eu and other lanthanides tend to involve expensive, stationary instruments and require time consuming sample preparation [2]. This work supports the development of a new method for identifying and quantifying lanthanides that can provide a fast, inexpensive, portable, and robust alternative.…”
Section: Introductionmentioning
confidence: 74%
“…Our group has shown this previously using 3.0 M KCl and 3.0 M NaNO 3, respectively [51,52]. To regenerate the film in this work, 3.0 M KCl was used.…”
Section: Spectroelectrochemistrymentioning
confidence: 74%